Insegurança alimentar, estado nutricional e hábitos alimentares de pessoas acometidas por hanseníase em municípios do interior da Bahia, 2001-2014 - Teixeira, Camila Silveira Silva (2017)
Food insecurity (FI) in vulnerable groups can result in damage to dietary habits and the nutritional status of individuals. Diseases such as leprosy, feed back the cycle of poverty and reduce the chances of human development, corroborating the food vulnerability of the affected people. The objective of the study was to characterize food insecurity, nutritional status and eating habits in people affected by leprosy. Cross - sectional study of 276 cases of leprosy reported in the Notifiable Diseases Information System, between 2001 and 2014, in the cities of Vitória da Conquista and Tremedal, located in the southwest region from Bahia. The FI was estimated through the Brazilian Scale of Food Insecurity. Anthropometric data, weight and height, and individual feeding frequency were collected. Household, socioeconomic, psychosocial and clinical variables were also evaluated. The association between the outcome and the explanatory variables of interest was estimated by Poisson regression with robust variance. The prevalence of FI was estimated at 39.4% (n=95) in Vitória da Conquista and 51.4% (n=18) in Tremedal; In these cities as, respectively, mild 27.8% (n=67) and 31.4% (n=11), moderate 7.5% (n=18) and 11.4% (n=4), and severe, 4.1% (n=10) and 8.6% (n=3). The estimated prevalence of overweight/obesity was 62.0% (n=132) in Vitória da Conquista and 46.7% (n=14) in Tremedal. There was a significant difference in relation to the excessive salt intake (p=0.008), milk consumption (p=0.002), cooked vegetables (p=0.001), raw vegetables (p=0.018) and fruits (p=0.001). In regression analysis a prevalence of IF was associated with the benefit of PBF (PR=3.09; CI95%: 1.80-5.40), development of reactional episode (PR=1.73; CI95%: 1.20-2.60), some dermatological effect on the quality of life (PR=1.50; CI95%: 1.05-2.14), some activity limitation (PR=1.38; CI95%: 0.95-2.34), external walls of the uncoated domicile (PR=1.38; CI95%: 1.01-1.91). The interactions between some activity limitation and benefit of PBF (PR=0.43; CI95%: 0.23-0.82) and development of reactional episode and benefit of PBF (PR=0.51; CI95%: 0.27-0.96). The subjects under study suffered from FI and had inadequate food habits and nutritional status. The physical, social and psychological impacts associated with leprosy over time may have affected living and health conditions, favoring household food vulnerability. It is recommended the insertion of nutritional assistance into public health policies as a way of qualifying attention to the person with leprosy, considering the negative impacts on the general health condition .